2011 IEEE International Conference on Industrial Engineering and Engineering Management 2011
DOI: 10.1109/ieem.2011.6117993
|View full text |Cite
|
Sign up to set email alerts
|

The role of time, cost and quality in project management

Abstract: Project management has emerged as a field of practice that is being used increasingly by organizations to achieve their business goals. Since the concept 'survival of the fittest' best describes today's business environment, good project management performance assessment tools are needed in order to make an organization 'the best of the best'. Project completion within time and cost, while maintaining quality is very important for the success of projects. Therefore, the purpose of this paper is to analyse the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Cost overruns are caused by inflation on materials (Olawale & Sun, 2018), time overruns (Solis-Carcano et al, 2015) and rework (Hwang, et al, 2009) Every project has an anticipated level of quality based on the details and specifications set out by the users (Stojcetovic, et al, 2013). According to Ng and Anuar (2011) quality performance is concerned with the quality of the project's final outcome and the quality objectives of the project. Mortaheb, et al (2012) observed that a project outcome has quality if it satisfies the client's overall expectations and if it achieves the technical specifications.…”
Section: Introductionmentioning
confidence: 99%
“…Cost overruns are caused by inflation on materials (Olawale & Sun, 2018), time overruns (Solis-Carcano et al, 2015) and rework (Hwang, et al, 2009) Every project has an anticipated level of quality based on the details and specifications set out by the users (Stojcetovic, et al, 2013). According to Ng and Anuar (2011) quality performance is concerned with the quality of the project's final outcome and the quality objectives of the project. Mortaheb, et al (2012) observed that a project outcome has quality if it satisfies the client's overall expectations and if it achieves the technical specifications.…”
Section: Introductionmentioning
confidence: 99%
“…The success of a released project depends much on the effective multidisciplinary effort, involving teams of people and support organizations that interact in a highly complex, intricate, and sometimes even chaotic way [13]. However, knowledge management has an important role as a source of competitive advantage, and it links very strongly to new product development for semiconductor manufacturing firms [14].…”
Section: Introductionmentioning
confidence: 99%
“…Where as, by observing, beyond common to all projects characteristics, peculiarities more than IT projects have, they were previously reported as the difficulty in measuring results, especially in software projects and difficulty in identifying requirements and monitor project progress and time estimates, one can say that most of the practices described refers to the process improvement, mainly software process such as RUP methodologies -Rational Unified Process [34,50], CMMI -Capability Maturity Model Integration [27,34], Metrics for Software Process, among others. Another example, in [6], can be verified using the Microsoft Office Project tool assisting in making appropriate decision with regard to time, cost and quality of the project. After all, from the practices identified one can assemble the array of judgment that will be used to pinpoint the best practices for managing IT projects.…”
Section: Practices In the Management Of It Projectsmentioning
confidence: 99%